Political Theory between Philosophy and Rhetoric Politics as Transcendence and Contingency - Ballacci, Giuseppe (Rhetoric, Politics and Society, 2018)
This book explores the significance of rhetoric from the perspective of its complex relationship with philosophy. It demonstrates how this relationship gives expression to a basic tension at the core of politics: that between the contingency of its happening and the transcendence toward which it strives. The first part of the study proposes a reassessment of the ancient quarrel between philosophy and rhetoric, as it was discussed by Plato, Aristotle, and above all Cicero and Quintilian, who ambitiously attempted to bring them together creating an ideal that is at the roots of the humanist tradition. It then moves to twentieth-century political theory and shows how the questions that emerge from that quarrel still strongly resonate in the works of key thinkers such as H. Arendt, L. Strauss, and R. Rorty. The volume thus offers an original contribution that locates itself at the intersection of politics, rhetoric, and philosophy.